2021
DOI: 10.1111/jgs.17276
|View full text |Cite
|
Sign up to set email alerts
|

Comment on: Family caregiver assessment in primary care: How to strengthen the healthcare triad?

Abstract: See the Reply by https://doi.org/10.1111/jgs.17277. in this issue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…In their comment, 1 Balsinha et al point out differences in the way family doctors in Portugal are viewed and practice medicine compared with primary care providers elsewhere, reminding us that primary care occurs within highly variable systems of medical care in countries throughout the world. Healthcare policies, especially regarding reimbursable services, might serve to encourage or restrict primary care providers to engage in family caregiver assessment.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…In their comment, 1 Balsinha et al point out differences in the way family doctors in Portugal are viewed and practice medicine compared with primary care providers elsewhere, reminding us that primary care occurs within highly variable systems of medical care in countries throughout the world. Healthcare policies, especially regarding reimbursable services, might serve to encourage or restrict primary care providers to engage in family caregiver assessment.…”
mentioning
confidence: 99%
“…To the Editor: We read with great interest the article by Van et al on geriatric co-management for cardiology patients. 1 They reported that nurse-led geriatric comanagement for cardiac patients over 75 years of age effectively reduced adverse events after hospitalization. We respect their careful evaluation of the comanagement process.…”
mentioning
confidence: 99%
See 2 more Smart Citations